2017
DOI: 10.1016/j.micromeso.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of external surface and pore mouth acid sites in unit-cell thick pillared MFI and pillared MWW zeolites

Abstract: The pillared MWW (PMWW or MCM-36) and pillared MFI (PMFI) zeolites consist of a single-or near single-unit-cell thick two-dimensional (2D) zeolitic layer structure. The concentrations of external surface and pore mouth Brønsted acid sites in these zeolites were quantified by a combined dimethyl ether (DME) titration and methanol dehydration in the presence of 2,6-di-tert-butylpyridine (DTBP) or triphenylphosphine (TPP), respectively. DME can access to all Brønsted acid sites in PMFI and PMWW zeolites and thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 59 publications
1
31
0
Order By: Relevance
“…The formation of the alkylation product, 1,3,5‐trimethyl‐2‐benzylbenzene, was found to be inhibited and eventually completely suppressed when an excess amount of dTBP was added in the reaction mixture . Since dTBP only deactivates BASs on the external surface of MFI, it can be concluded that only the external BASs of SPP are accessible to catalyze the alkylation reaction. Control experiments were carried out using pure‐silica SPP (a pure‐silica zeolite with SPP structure), γ‐alumina (a Lewis acid catalyst), and Sn‐SPP (a Lewis acid zeolite with SPP structure).…”
Section: Resultsmentioning
confidence: 99%
“…The formation of the alkylation product, 1,3,5‐trimethyl‐2‐benzylbenzene, was found to be inhibited and eventually completely suppressed when an excess amount of dTBP was added in the reaction mixture . Since dTBP only deactivates BASs on the external surface of MFI, it can be concluded that only the external BASs of SPP are accessible to catalyze the alkylation reaction. Control experiments were carried out using pure‐silica SPP (a pure‐silica zeolite with SPP structure), γ‐alumina (a Lewis acid catalyst), and Sn‐SPP (a Lewis acid zeolite with SPP structure).…”
Section: Resultsmentioning
confidence: 99%
“…The acid site accessibility of pillared MFI and SPP zeolites has been measured by direct DTBP uptake measurements, which maintain the characteristics of the high acid site accessibility in 2D MFI zeolites [173,245,251,252]. In particular, the concentrations of external surface and pore mouth Brønsted acid sites in the pillared MFI zeolite was quantified by a combined dimethyl ether (DME) titration and methanol dehydration in the presence of DTBP or triphenylphosphine (TPP) titrants, respectively [232]. DME can access all Brønsted acid sites in pillared MFI zeolites and thus determine the total number of acid sites.…”
Section: Acidity Characterization For 2d Mfi Zeolitesmentioning
confidence: 99%
“…It can solely access the acid sites on the external surface [271]. The decrease in methanol dehydration rate in the presence of TPP titrant reflects the fractions of external surface and/or pore mouth acid sites in MCM-36 zeolite, where it consists of ∼33% external surface and ∼31% pore mouth acid sites [232]. 31 P MAS NMR spectroscopy was used to analyze acid site locations in the 2D MIT-1 structure [67].…”
Section: Acidity Characterization For 2d Mww Zeolitesmentioning
confidence: 99%
“…A deeper differentiation and quantification of external acid sites located on the external surface or at the pore mouth regions in pillared MFI and MWW materials was performed by Wu et al In addition to the titration with dimethyl ether to evaluate overall acid site concentration, methanol dehydration in the presence of 2,6‐di‐ tert ‐butylpyridine or triphenylphosphine was tested. While 2,6‐di‐ tert ‐butylpyridine (with a diameter of 7.9 Å) can access both the acid sites on external surface and at the pore mouths, triphenylphosphine (with a diameter of 9.4 Å) can only access the former.…”
Section: D Zeolitesmentioning
confidence: 99%